Profile of teacher and guidance counselor training in public school in Galicia - Sanjuán Roca, María del Mar (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
The aim of this paper is to present the academic and professional profile for teachers of Training Module and Employment Guidance, for that we will display data from a study (Sanjuán, 2008) that was carried out during the academic year 2006-2007 in the public schools in Galicia. We will show how was the initial and in-service training of the teachers, differences in the level of qualification and specialty; also, we anal yze the voluntarism that was subject to their teacher training and, finally, we shall see how in-service training has a different treatment.